Establishment of gastrointestinal epithelial organoids - Mahé, Maxime M (2013)
The intestinal epithelium constitutes a system of constant and rapid renewal triggered by proliferation of intestinal stem cells (ISCs), and is an ideal system for studying cell proliferation, migration and differentiation. Primary cell cultures have proved to be promising to unravel the mechanisms involved in the epithelium homeostasis. In 2009, Sato et al. established a long-term primary culture to generate epithelial organoids (enteroids) with crypt- and villus-like epithelial domains representing the complete census of progenitors and differentiated cells. Similarly, isolated ISCs expressing Lgr5 (Leucine-rich repeat-containing G protein-coupled receptor) could generate enteroids. Here, we describe methods to establish gastric, small intestinal, and colonic epithelial organoids (Basic Protocol 1) and the generation of Lgr5(+ve) single cell-derived epithelial organoids (Basic Protocol 2). We also describe the imaging techniques used to characterize those organoids (Basic Protocol 3). This in vitro model constitutes a powerful tool for studying stem cell biology and intestinal epithelial cell physiology throughout the digestive tract.